On the origins of the Franco-German EMU controversies - Ivo Maes (National Bank of Belgium, 2002)
EMU is, to a large extent, the result of a process of Franco-German reconciliation and understanding. However, in the postwar period, there were significant differences in ideas and economic policy-making in Germany and France. France was dominated by the "tradition républicaine", giving a central role to the state in economic life. In Germany, the federal structure of the state went together with the social market economy. In this paper an analysis is presented of these differences in thought and economic policy-making, how they evolved through time, and how they contributed to shaping the nature and form of the European Union. The focus is on the Rome Treaties, the Werner Report and the Maastricht Treaty process.
Keywords: A11; B20; E58; F02; P16; 330; EMU; economic thought; economic policy-making; France; Germany; Währungsunion; Staatliche Einflussnahme; Ordnungspolitik; Deutschland; Frankreich